PERKEMBANGAN POLA PERMUKIMAN MASYARAKAT KAMPUNG MELAYU - AGUS VIESTO CHILMY; KARYA WIDYAWATI (Faktor Exacta, 2013)
Malay village is located around the village of Jatinegara that originally inhabited by the Malay Peninsula immigrants from Malacca (now Malaysia). Position Jatinegara a very strategic area for a band meeting between various public transport to move around the corner of Jakarta and the increasing urbanization of society to Jakarta, causing the increasing population density in Kampung Melayu. Immigrants who come from outside Jakarta with the capacity and limited membership can not afford to buy land in Jakarta that the higher price, then they live and develop semi-permanent houses on land on the outskirts of the outskirts like rail-rail and river bantaran. The larger number of immigrants already caused them to develop their home by the time the Ciliwung. Higher density region awakened from time to time accompanied by a decrease environmental quality. To describe how patterns of development of Kampung Melayu retreat from Holland to the present time and discover the factors that cause the development pattern occurs then this study was conducted. Keywords: Growth, patterns, settlement, village